2016
DOI: 10.17533/udea.rccp.v29n2a07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corn oil on the gastric mucosa of horses with induced ulcer

Abstract: SummaryBackground: equine gastric ulcer syndrome (EGUS) has a multifactorial nature and it affects both the squamous and glandular mucosa of the stomach. Multiple therapeutic strategies involving large periods of medication are used to treat this condition. Objective: to evaluate the effects of administering corn oil (CO) to horses with induced gastric ulcers, and to describe the mechanism of action of the mucosal repair. Methods: fifteen horses divided into three groups were used. A combination of confinement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…The results of the present study are consistent with and build on previous studies suggesting that decreased basal glandular gastric PGE 2 concentrations may not be a key contributor to NSAID‐induced glandular gastric lesions in the horse (Martínez Aranzales et al., ; Martínez et al., ; Meschter et al.,).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study are consistent with and build on previous studies suggesting that decreased basal glandular gastric PGE 2 concentrations may not be a key contributor to NSAID‐induced glandular gastric lesions in the horse (Martínez Aranzales et al., ; Martínez et al., ; Meschter et al.,).…”
Section: Discussionsupporting
confidence: 92%
“…A recent series exploring PGE 2 concentrations in gastric contents following phenylbutazone administration did not observe a decrease in released PGE 2 (Martínez Aranzales, Cândido de Andrade, & Silveira Alves, 2015;Martínez, Zuluaga, & Silveira, 2016). However, concentration in the gastric fluid may not necessarily reflect concentration within the gastric mucosa, and it is likely that mucosal concentrations are most critical to development of gastric lesions.…”
mentioning
confidence: 99%
“… 144 A more recent study found that corn oil did not have any effect on healing in the squamous mucosa following phenylbutazone-induced ulceration. 145 The addition of oil may be useful in replacing calories when transitioning away from a high starch diet.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Supporting this, a combined omeprazole and sucralfate therapy for the treatment of EGGD is superior to omeprazole alone [ 148 ]. The recommended dose is currently 12 mg/kg PO bis in die (BID—twice a day) [ 1 ], although many authors report doses up to 20 or 30 mg/kg three to four times per day [ 97 , 149 ]. Comparisons of the clinical efficacy of different doses and frequency on naturally occurring disease have not been reported.8.3.…”
Section: Treatmentmentioning
confidence: 99%